Discordance in risk perception between children, parents, and teachers in terms of consumption of cheap and poorly nutritious food sold around schools. (June 2015) - Kim, Nam Hee; Kim, Min Jung; Park, Byoung Il; Kang, Yun Sook; Hwang, In Gyun; Rhee, Min Suk
Highlights: Significant gap between children's food risk perception and eating practices. Existing education does not provide children with adequate information. Differences in the perception of cheap and poorly nutritious foods sold around school between children and adults. More child-driven strategies are needed for food safety education. Educational programs aimed at parents and teachers are required. Abstract: Little is known about the eating behavior of Asian children when faced with a range of poorly nutritious foods sold around schools, and whether they appreciate the risks involved in consuming such foods. To provide adequate education regarding proper food consumption, it is essential to understand how children perceive the potential risks and to examine their actual eating behaviors. The perceptions of adults and children should also be compared. This study selected children from the most populous primary schools ( n = 166) in 36 of the national capital regions of the Republic of Korea. A total of 443 children were randomly selected from each school and they, their parents ( n = 425), and nutrition teachers ( n = 166) were asked to complete a questionnaire (total 11 questions) designed to examine how children and adults perceived the risks associated with the consumption of cheap and poorly nutritious foods sold around schools. Most children (>70%) consumed these foods more than once per week, even though they were aware that they may be potential hazardous. Children were significantly less concerned about the risks associated with their eating behaviors than their parents and teachers ( p < 0.05), particularly regarding snacks prepared and cooked under unhygienic conditions. Although parents and teachers were very concerned about children's food consumption, they misunderstood the level of children's awareness, their preferences, and their actual eating behaviors. This study generated a database of information about children's actual eating behavior around schools, and the perception (by children, parents, and teachers) of the risks. This database may contribute to the design of suitable educational programs for children, parents, and teachers.